Photocarrier‐Induced Active Control of Second‐Order Optical Nonlinearity in Monolayer MoS2. Issue 5 (14th January 2020) - Taghinejad, Mohammad; Xu, Zihao; Wang, Hua; Taghinejad, Hossein; Lee, Kyu‐Tae; Rodrigues, Sean P.; Adibi, Ali; Qian, Xiaofeng; Lian, Tianquan; Cai, Wenshan
Abstract: Atomically thin transition metal dichalcogenides (TMDs) in their excited states can serve as exceptionally small building blocks for active optical platforms. In this scheme, optical excitation provides a practical approach to control light‐TMD interactions via the photocarrier generation, in an ultrafast manner. Here, it is demonstrated that via a controlled generation of photocarriers the second‐harmonic generation (SHG) from a monolayer MoS2 crystal can be substantially modulated up to ≈55% within a timeframe of ≈250 fs, a set of performance characteristics that showcases the promise of low‐dimensional materials for all‐optical nonlinear data processing. The combined experimental and theoretical study suggests that the large SHG modulation stems from the correlation between the second‐order dielectric susceptibility χ (2) and the density of photoexcited carriers in MoS2 . Indeed, the depopulation of the conduction band electrons, at the vicinity of the high‐symmetry K/K′ points of MoS2, suppresses the contribution of interband electronic transitions in the effective χ (2) of the monolayer crystal, enabling the all‐optical modulation of the SHG signal. The strong dependence of the second‐order optical response on the density of photocarriers reveals the promise of time‐resolved nonlinear characterization as an alternative route to monitoring carrier dynamics in excited states of TMDs. Abstract : Depopulation of the conduction band electrons via an optical means diminishes the contribution of interband electronic transitions in the effective second‐order nonlinear response of monolayer transition metal dichalcogenides (TMDs). The intrinsic decay of photocarriers adds the element of time dependency to the nonlinear response of TMDs, facilitating the active control of nonlinear frequency generation in an all‐optical manner.